2020
DOI: 10.17784/mtprehabjournal.2018.16.562
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-citrulline malate oral supplementation on post-exercise hypotension

Abstract: Background: L-citrulline malate supplementation promotes an increase in oxide nitric metabolites, which are considered important mediators of peripheral vasodilation. Thus, the supplementation with this substance might maximize the duration and magnitude of post-exercise hypotension. Objectives: To investigate the hypotensive effect of L-citrulline malate supplementation following a single session of aerobic exercise in normotensives. Methods: Forty adults, normotensives, sedentary, were randomly assigned to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…While the present study showed improvement in resting diastolic BP after seven days of supplementation, there were no changes observed in systolic BP in either treatment condition. Two investigations specifically report that after CIT supplementation, systolic BP was significantly lowered, while no differences in diastolic BP were found for either group at any time point in these studies 7,23 . In addition, some studies found that systolic BP lowered for older men along with diastolic BP, without any effect found in older women 2,17 .…”
Section: Discussionmentioning
confidence: 84%
“…While the present study showed improvement in resting diastolic BP after seven days of supplementation, there were no changes observed in systolic BP in either treatment condition. Two investigations specifically report that after CIT supplementation, systolic BP was significantly lowered, while no differences in diastolic BP were found for either group at any time point in these studies 7,23 . In addition, some studies found that systolic BP lowered for older men along with diastolic BP, without any effect found in older women 2,17 .…”
Section: Discussionmentioning
confidence: 84%